BIOPHYSICAL SCREENING OF BRINJAL GENOTYPES AGAINST FRUIT AND SHOOT BORER, LEUCINODES ORBONALIS (GUEN.) - LAKSHMAN CHANDRA PATEL; AMITAVA KONAR; CHANDRA SEKHAR SAHOO (The Bioscan, 2015)
The effect of nine biophysical parameters of twenty nine genotypes of brinjal was tested against shoot and fruit borer (SFB). The lowest damage on shoots (1%) and fruits (4%) occurred in 12/SPT BL VAR 7 followed by statistically at par Punjab Sadabahar with damage of 1.2 and 5.2%, respectively. While the highest damage on shoots (6.2 %) and fruits (22.8 %) found in 12/SPT BL VAR 10, succeeded by statistically at par 12/SPT BL VAR 9 with 6 and 22.5% damage, respectively. The correlation of fruit damage was positively strong with fruit girth (r = 0.638), pedicel length (r = 0.444) and fruit numbers (r = 0.014), but negatively strong with fruit length (r = - 0.343). The non significant positive correlations were found with canopy length (r = 0.059), days to 1st flowering (r = 0.017), mean fruit weight (r = 0.106) and yield (0.075). Six genotypes viz. 12/SPT VAR 8, Punjab Sadabahar, 13/BRL VAR 5, 12/SPT BL VAR 7, 12/SPT BR VAR 6 and 12/SPT BL VAR 5; two genotypes viz. 12/SPT BL VAR 10 and 12/SPT BL VAR 9 and rest twenty one genotypes were recognized respectively as highly resistant, tolerant and fairly resistant.